Improving Image‐Guided Surgical and Immunological Tumor Treatment Efficacy by Photothermal and Photodynamic Therapies Based on a Multifunctional NIR AIEgen. Issue 22 (26th April 2021) - Jiang, Ruming; Dai, Jun; Dong, Xiaoqi; Wang, Quan; Meng, Zijuan; Guo, Jingjing; Yu, Yongjiang; Wang, Shixuan; Xia, Fan; Zhao, Zujin; Lou, Xiaoding; Tang, Ben Zhong
Abstract: Multimodal therapy is attracting increasing attention to improve tumor treatment efficacy, but generally requires various complicated ingredients combined within one theranostic system to achieve multiple functions. Herein, a multifunctional theranostic nanoplatform based on a single aggregation‐induced‐emission luminogen (AIEgen), DDTB, is designed to integrate near‐infrared (NIR) fluorescence, photothermal, photodynamic, and immunological effects. Intravenously injected AIEgen‐based nanoparticles can efficiently accumulate in tumors with NIR fluorescence to provide preoperative diagnosis. Most of the tumors are excised under intraoperative fluorescence navigation, whereafter, some microscopic residual tumors are completely ablated by photodynamic and photothermal therapies for maximally killing the tumor cells and tissues. Up to 90% of the survival rate can be achieved by this synergistic image‐guided surgery and photodynamic and photothermal therapies. Importantly, the nanoparticles‐mediated photothermal/photodynamic therapy plus programmed death‐ligand 1 antibody significantly induce tumor elimination by enhancing the effect of immunotherapy. This theranostic strategy on the basis of a single AIEgen significantly improves the survival of cancer mice with maximized therapeutic outcomes, and holds great promise for clinical cancer treatment. Abstract : Integrated surgery and phototheranostics employing nanoparticles based on a near‐infrared aggregation‐induced emission luminogen (AIEgen) for image‐guided synergistic tumor therapy are explored to overcome respective limitations and realize maximized therapeutic outcomes and minimized recurrences. Moreover, the combined treatment of AIEgen‐nanoparticle‐mediated phototheranostics and programmed death‐ligand 1 antibody significantly induces tumor elimination by enhancing the effect of immunotherapy.